2004
DOI: 10.1161/01.res.0000136816.05109.89
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Voltage-Gated Sodium Channel Na v 1.5 Is Regulated by Nedd4-2 Mediated Ubiquitination

Abstract: Abstract-Na v 1.5, the cardiac isoform of the voltage-gated Na ϩ channel, is critical to heart excitability and conduction. However, the mechanisms regulating its expression at the cell membrane are poorly understood. The Na v 1.5 C-terminus contains a PY-motif (xPPxY) that is known to act as binding site for Nedd4/Nedd4-like ubiquitin-protein ligases. Because Nedd4-2 is well expressed in the heart, we investigated its role in the ubiquitination and regulation of Na v 1.5. Yeast two-hybrid and GST-pulldown exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
200
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(219 citation statements)
references
References 36 publications
17
200
1
1
Order By: Relevance
“…Because both epithelial sodium channel and cystic fibrosis transmembrane conductance regulator are Nedd4-2 substrates (30,47), it is likely that Rab4 also regulates these two channels via Nedd4-2. In addition, cardiac and neuronal Na ϩ channels, cardiac K ϩ channel KCNQ1, and neuronal K ϩ channels KCNQ2/3/5 are among the substrates of Nedd4-2 (32)(33)(34)48). Besides the direct effects on these channels, Rab4 is expected to regulate these channels via altered Nedd4-2 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because both epithelial sodium channel and cystic fibrosis transmembrane conductance regulator are Nedd4-2 substrates (30,47), it is likely that Rab4 also regulates these two channels via Nedd4-2. In addition, cardiac and neuronal Na ϩ channels, cardiac K ϩ channel KCNQ1, and neuronal K ϩ channels KCNQ2/3/5 are among the substrates of Nedd4-2 (32)(33)(34)48). Besides the direct effects on these channels, Rab4 is expected to regulate these channels via altered Nedd4-2 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…The external and internal solutions used were as previously described (ref. 23 and see Supplemental Methods). Data were recorded using a VE-2 amplifier (Alembic Instruments) or an Axon 700A amplifier and analyzed using pClamp software, version 8 (Molecular Devices), KaleidaGraph, version 4.03 (Synergy Software), and MATLAB (The MathWorks).…”
Section: Electrophysiologymentioning
confidence: 99%
“…All Na v isoforms, except Na v 1.4 and Na v 1.9, possess a PY motif and are potential targets of NEDD4-2. In vitro experiments have indicated that NEDD4-2 can negatively regulate the epithelial sodium channel ENaC (22) and Na v s (23,24). The functional relevance of NEDD4-2 in sensory neurons, as well as its possible involvement in pain sensitivity, have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…MOG1, 14-3-3 ␤ and ankyrin-G regulate Na v 1.5 localization to the cell surface in cardiomyocytes (4,7). Nedd4-2 interacts with Na v 1.5 and regulates Na v 1.5 degradation (8). However, the Na v 1.5 protein complex is highly sophisticated.…”
mentioning
confidence: 99%